Naringina promove efeito inotrópico positivo dependente de catecolaminas endógenas em coração isolado de rato - Santos, Leonardo Rodrigues dos (2016)
Naringin is a flavonoid glycoside (C27H32O14) found in citrus fruits and grapes, recognized for exercising antioxidant, antiatherogenic, hypoglycemic activity, among others. Contractile and electrical effects of naringin were characterized on the heart muscle of rats. The experiments were performed in the left atrium isolated rat (tub with 8 ml, Krebs-Hanseilet, 29 ± 0.1 ° C; Stimulation: 1 gf, 1 Hz, 100 V, 1.5 ms). The force data were obtained by isometric transducer (Grass FT03), amplified (Grass P11T), digitized (DATAQ DI710) and stored in a computer for analysis. The naringin (0.003 to 6 mM) was added cumulatively to the bath to determine their influence on the contractile parameters. Curves concentration-effect of naringin were obtained after atrial preincubation with 1 uM propranolol or 1 uM nifedipine or 1 uM ryanodine or still, using atria of animals with depletion of catecholamine. The effect of naringin on electrocardiograms were obtained by Langendorff technique (10 ml / min - Milan peristaltic pump; Krebs solution at 34 ± 0.1 °C aerated with carbogen), with measurement of the left intraventricular pressure (PVE) by inserting the balloon. Data were expressed as mean ± standard error of the mean and the results were evaluated by one-way analysis of variance (ANOVA) with Tukey post test or Student t test. P values ≤ 0.05 were considered significant and statistical analyzes were performed with the GraphPad Prism© version 5.0 (GraphPad Software Inc., San Diego CA, USA). Naringin (0.03-2 mM) induced a positive inotropic effect on atrium (147%; EC50 of 0.32 ± 0.01 mM, n=5) dependent on concentration. From 3 mM, naringin reduced the contractile force. At maximum positive inotropic effect of naringin there was a decrease of systole duration of 0.11 ± 0.006 sec to 0.09 ± 0.002 sec (p <0.05) and increase in the diastole duration of 0.84 ± 0.019 sec to 0.88 s ± 0.0024 sec (p <0.05). Observed increase dT/dt (+) of 6.16 ± 1.76 gf/sec to 19.74 ± 2.64 gf/sec (p <0.01) and dT/dt (-) of 6.21 ± 1.14 gf/sec to 13.52 ± 1.78 gf /sec (p <0.01). Naringin also promoted diastolic relaxation (44%). Preincubation of the atria with propranolol (Non-selective β-adrenoceptor antagonist) or nifedipine (L- type calcium channels antagonist) or ryanodine (ryanodine receptors antagonist) abolished the positive inotropic effect induced by naringin, as well as no detectable increase in contractile force in atria of animals with depletion of catecholamines. With regard to electrical parameters, naringin shortened PRi of 48.42 ± 0.81ms to 47.31 ± 0.89ms (n = 5, p <0.05) and reduced QT intervals (QTc) of 66, 75 ms ± 2.35 to 64.36 ± 2.24 ms. Conversely, the QRS complex increased (Control: 18.5 ± 1.0 ms and Naringin: 20.83 ± 1.24 ms). This flavonoid also influenced the activity of the cardiac pacemaker, increasing heart rate of 226.9 ± 1.12 bpm to 240.2 ± 3.94 bpm. No cardiac arrhythmia event was recorded during the perfusion of the heart with naringin. The PVE suffered increase of 6%. Naringin exerts positive inotropic and chronotropic effect on cardiac muscle by indirect activation of β-adrenergic receptors through endogenous catecholamines release and promotes significant electrocardiographic changes, reducing PRi, QTc and RRi, and slow down the speed of the QRS.